Variations on soil protection in a test of provenances of Pinus greggii Engelm. in El Potosí Hill, Galeana, Nuevo León - Rodríguez-Laguna, Rodrigo; Meza-Rangel, Joel; Vargas-Hernández, Jesús; Jiménez-Pérez, Javier (Instituto de Ecología, A.C., 2016)
With the purpose of knowing the soil protection that tree crowns provide in a test of provenances of Pinus greggii Engelm. planted 4.5 years prior to the test in the Cerro El Potosí, Galeana, Nuevo León, survival, height and crown characteristics were measured; crown projection area, luminance interception area and percentage of crown were also calculated. No significant difference was found between provenances in the survival, but in general it was found a survival rate of 93%; however, there were significant differences (P≤0,05) in height, height at the first branch, height to the wide point of the crown, crown projection area, luminance interception area and percentage of crown. The trees of the provenances with greater crown projection area had 0,85 m2 and in the luminance interception area varied in more of 1,1 m2 between the provenances extremes. For the crown percentage the higher value obtained was of 89,1% of stems with crown. The components of variance showed that provenances provided 7.5% of the total variation in crown projection area and in the crown diameter. On the other hand, this value diminished for height at the first branch and height to the wide point of the crown with 5,2% and 2,9%, respectively. After 4,5 years of establishing the test, the crowns of trees have covered 14,8% of the total surface planted. The tree growth was positively correlated with the luminance interception area (r = 0,94), crown projection area (r = 0,86) and percentage of crown (r = 0,48). The study shows evidences to select the provenance of Los Lirios, Coahuila and Agua Fría, Nuevo León as the best choices to protect the soil at the planting site.